Criterion for the Quantitative Assessment of Ideal Conditions in Chromatography - A. V. Larin (Adsorption Science & Technology)
The quantitative relationship between the plate theory variant model of equilibrium adsorption in which time is the only independent variable and the theory of ideal chromatogaphy has been evaluated. It has been shown that an approach to ideal conditions depends directly on an increase in the relative (or absolute) length of the column. Practical recommendations on the choice and assessment of conditions to verify the measurement of adsorption isotherms and on the calculation of chromatographic processes in accordance with the theory of ideal chromatography are given.